Inflation Targets Versus International Monetary Integration - A Canadian Perspective - David Laidler (Center for Economic Studies and ifo Institute (CESifo), 2002)
The debate about Canadian-U.S. monetary integration is surveyed. The choice is among overall monetary orders,rather than exchange rate regimes and questions of policy credibility and political accountability are crucial. Canada's recent economic performance under inflation targets, and arguments that the flexible exchange rate has undermined real economic performance are assessed. The most economically attractive among alternative monetary orders, the adoption by Canada of the US dollar with provision for meaningful Canadian input into policy decisions and supervision of the financial system - is not politically attainable. Intermediate arrangements are unattractive and clearly inferior to Canada's current monetary order.
Keywords: E42; E52; E58; F33; 330; monetary policy; exchange rates; central banks; inflation.